Beyond user control and two-way communication: the four-factor model of interactivity of wrist-worn smart devices - Kang, Hyunjin (2022)
Wrist-worn smart devices such as smartwatches and smart health trackers have transformed the way we interact with technology. Whereas they share some commonalities with prior interactive media like smart phones, there are new interactivity elements of wrist-worn smart devices such as networking personal media and devices, adapting to personalized needs, and nudging healthy behavior. In order to investigate how these new factors can afford a unique interaction experience, the current study develops a user-driven conceptualization of interactivity in wearable technology. In Study 1, through an interview and a survey with wrist-worn smart device users, four factors that comprise interactivity of wrist-worn smart devices are identified: networking, adaptive, nudging, and multisensory. Exploratory and confirmatory factor analyses are conducted to examine the four-factor structure of interactivity and demonstrate strong reliability and convergent validity among the proposed factors. Study 2 revalidates the measurement structure of interactivity developed in Study 1 and further tests the theoretical value of the four-factor model by examining how the four factors predict usage intention mediated by hedonic and utilitarian benefits. Theoretical and practical implications are discussed.